Spectroscopic characterization of cadion: UV–vis, resonance Raman and DFT calculations of a versatile metal complexing agent. (21st December 2012) - Lepre, Luiz F.; Inoue, Fabiana; Corio, Paola; Santos, Paulo S.; Ando, Rômulo A.
Abstract : The spectroscopic characterization of cadion or 1‐(4‐nitrophenyl)‐3‐(4‐phenylazophenyl)triazene, its anionic species and its complexes with Hg 2+, Cd 2+ and Ni 2+ in DMSO solution is presented. Resonance Raman (RR) and UV–vis spectroscopy were the techniques of choice with results supported by density functional theory calculations. As previously reported, the UV–vis data indicate distinct absorption spectra for the five species mentioned, allowing for spectrophotometric metal differentiation. In order to understand the electronic spectra of such species, we performed a detailed RR investigation, where the spectral profiles revealed the vibrational modes mainly involved in the chromophoric moieties. The distinct enhancement profile observed for each species suggests that the charge transfer from the π‐system to the electron withdrawing NO2 group is modulated by the electron donating triazene moiety, depending on the metal attached. The results reported herein show that RR spectroscopy can be potentially used in the metal detection of multicomponent samples by the proper choice of the excitation wavelength. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : It is presented the resonance Raman characterization of cadion as neutral and anionic species and of its complexes with Hg 2+, Cd 2+ and Ni 2+ . The distinct resonance enhancement profiles show how Raman spectroscopy can be used to distinguish toxic metals by the proper choice of the excitation wavelength.